Arboristični vidiki snegoloma v mestni občini Ljubljana v zimi 1999 - Marion, Lena (Zbornik gozdarstva in lesarstva, 2005)
As a result of heavy snow in February 1999, trees were damaged in the City of Ljubljana, Slovenia. Of the investigated 624 trees, 195 (31%) were damaged by snow. On average, 1.7 branch and top per tree were broken. Snow damaged 17 tree species, affecting particularly Aesculus hippocastanum L. and, to a lesser extent, Betula pendula ROTH. and Salix x sepulcralis SIMONK. Decay was the most frequent defect at the failure location and was often associated withincluded bark and vicinity of old mechanical wounds. 87% of broken branches and tops with diameter exceeding 20 cm were decayed at failure location. The research showed that failures were associated rather with structural growth defects and wood decay than with tree species. Broken parts of half of all damaged trees impeded the traffic or caused material damages. Regular control of the trees' safety stage would enable early identification and removal of potentially hazardous trees and their parts. The research demonstrates a necessity for a systematic tree control and proper urban tree care in the City of Ljubljana.
Keywords: arboristika; drevje; Ljubljana; poškodbe dreves; snegolom